Corrosion : protection of structural metals and alloys (2019-2020) - Fürbeth, Wolfram; Kolisnychenko, Stanislav (Specialized collections ;, 2021)
This issue from the topic series "Corrosion" contains articles published by Trans Tech Publications in the 2019 - 2020 years. The volume "Corrosion. Protection of Structural Metals and Alloys (2019-2020)" is the second book on this topic and presents readers with a wide range of research results and engineering solutions in providing anti-corrosion protection of structural metals, alloys, and engineering objects. This collection will be valuable and exciting to a broad audience of researchers and engineers from various modern manufacturing areas. Corrosion, Passivation, High-Temperature Corrosion, Corrosion Resistance, Corrosion Protection, Coatings, Electrochemical Behaviour, Conversion Coating, Conversion Treatment, Corrosive Environment, Surface Treatment, Corrosion Inhibitor, Steel, Alloy, Electrophoretic Deposition, Anti-Corrosive Paint, Electroplating, Oxide Film, Electrodeposition, Anodising, Plasma-Electrolytic Oxidation, Micro-Arc Oxidation, Galvanising, Self-Healing Materials Science, Mechanical Engineering, Manufacturing.